The Effect of Co-Branding Strategy on the Brand Equity of Walls Cornetto Selection Silverqueen (Study On Walls X Silverqueen Collaboration) - Rahman, Diva Marshanda Putri (Asosiasi Ahli Administrasi Indonesia, 2022)
In today's increasingly competitive business environment, many companies are striving to enhance their product superiority to strengthen their brand image and maintain customer loyalty. One of the ways to achieve this is by implementing co-branding strategies. This study aims to examine the impact of the co-branding strategy on the brand equity of Wall's Selection Silverqueen products, focusing on the collaboration between Wall's and Silverqueen companies. The research adopts a quantitative approach, utilizing a questionnaire as the data collection method with a sample of 125 respondents who are students of Bandung State Polytechnic and have consumed Wall's Selection Silverqueen ice cream. The data is analyzed using techniques such as validity and reliability tests, descriptive analysis, normality tests, and simple linear regression analysis. The findings of this study reveal that the co-branding strategy has a significant and positive influence of 58.1% on brand equity. However, it should be noted that 41.9% of the brand equity is influenced by other factors not examined in this study.